My garden - Henkes, Kevin (New York : Greenwillow Books, 2010)
After helping her mother weed, water, and chase the rabbits from their garden, a young girl imagines her dream garden complete with jellybean bushes, chocolate rabbits, and tomatoes the size of beach balls.
Booklist
Pub Weekly
School Library Journal starred
Booklist, January 2010
Pub Weekly, January 2010
School Library Journal starred, March 2010
Keywords: Gardens -- Juvenile fiction; Imagination -- Juvenile fiction; Gardens -- Fiction; Imagination -- Fiction; Gardens -- Fiction; Imagination -- Fiction; Picture books for children